Carbeto de silício reforçado com fibras de Hi-Nicalon tipo S como revestimento de reatores PWR - avaliação neutrônica - Rochkhudson Batista de Faria (2017)
In this study, Silicon Carbide reinforced with Hi-Nicalon type S fibers (SiC HNS) (proposed), was simulated as a nuclear fuel cladding of a PWR reactor, as well as the guide tubes. The results were compared with the Zircaloy cladding (conventional). From the neutron point of view, the SiC HNS was analyzed in the steady state and during the evolution of the fuel. From a thermal point of view, it was evaluated for its heat transfer in the core of the reactor and in a cooling vessel after irradiation. To validate the methodology used, a benchmark fuel element (ECB) was simulated. Thereafter, the conventional cladding of the fuel was replaced by the SiC HNS. The results showed the need for a thermal evaluation, since, for the neutronic calculations, it was necessary to use a mean operation temperature for each simulated material. In order to evaluate the average temperature of operation of the fuel, the cladding and the moderator, the code RELAP5 was used. A simplified reactor core model of the Angra II plant was used in the thermo-hydraulic study that simulated separately the behavior of the coatings (Zircaloy and SiC HNS). Thus, the study was extended and the same methodology was applied to the reactor core of Angra II, where variations in boron and burnable poison compositions were evaluated, as well as the conversion ratio (C) during the evolution of the fuel. Neutronic analyzes were performed using the SCALE 6.0 system (Standardized Computer Analysis for Licensing Evaluation). Finally, an ECB fuel rod after its total burn was analyzed via ANSYS computational code in terms of heat transfer, fuel for the claddings, Zircaloy and SiC HNS, and the claddings for the cooling water after irradiation.